2005
DOI: 10.5172/conu.19.1-2.96
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses' knowledge of evidencebased practice: Constructing a framework to evaluate a multifaceted intervention for implementing EBP

Abstract: Critical reflection upon nursing practice is pivotal in achieving optimal patient outcomes. Implicit in this statement is knowledge about and an understanding of the implementation of evidence-based practice (EBP). This study sought to evaluate baseline knowledge in order to assess and inform a multifaceted intervention to promote EBP in a multi-site facility in Western Sydney, Australia. On two consecutive days in February 2003, a convenience sample of 229 nurses were surveyed using a five-item, investigator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…However, several researchers have suggested that nurses have not reached a consensus about what EBP is (DiCenso et al 1998; Rolfe 1999; Lomas et al 2005). Many nurse researchers have also based their research on the medical definition and then focused on nurses' awareness of the accepted concept or the barriers nurses encounter in using research evidence (e.g., Kajermo et al 1998; Rosswurm & Larrabee 1999; Newman et al 2000; French et al 2002; Mohide & King 2003; Bahtsevani et al 2005; Mott et al 2005; Gerrish et al 2007). Some nurse authors have also tried to define evidence‐based nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, several researchers have suggested that nurses have not reached a consensus about what EBP is (DiCenso et al 1998; Rolfe 1999; Lomas et al 2005). Many nurse researchers have also based their research on the medical definition and then focused on nurses' awareness of the accepted concept or the barriers nurses encounter in using research evidence (e.g., Kajermo et al 1998; Rosswurm & Larrabee 1999; Newman et al 2000; French et al 2002; Mohide & King 2003; Bahtsevani et al 2005; Mott et al 2005; Gerrish et al 2007). Some nurse authors have also tried to define evidence‐based nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…A US study had similar findings (Melnyk et al 2004). In an Australian study, Mott et al (2005) found the lack of knowledge to be an obstacle to EBP. Many of these studies were conducted during or following EBP implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 229 practicing nurses showed that only 62% recognized the term EBP whereas 38% were not sure what it meant. The same study noted that only 42% could identify sources for best practice evidence (Mott et al, 2005). Common barriers to using EBP in healthcare organizations have been identified in multiple studies (Clifford & Murray, 2001;Dunn, Crichton, Roe, Seers, & Williams, 1997;Gerrish & Clayton, 2004;Jeffers et al, 2008;Newhouse, Dearholt, Poe, Pugh, & White, 2005;Parahoo, 2000;Pravikoff, Tanner, & Pierce, 2005;Zeitz & McCutcheon, 2005).…”
Section: Background Ebpmentioning
confidence: 83%